The Effect of Agglomeration Strategy on Rural Resilience from the Perspective of Homestay Tourism Operators - Ye Chongliang; Miao Xumei; Granovskaya Olga; Sun Feihan (Journal of Economy Culture and Society)
Homestay tourism villages (HTVs) represent a path for the transformation, revitalization, and sustainability of rural communities. However, due to the risks inherent in homestay tourism, they are often vulnerable to internal and external environmental changes which derive from the fragility and instability of integration of rural culture and tourism, unstable outcomes of science and technology, etc. Resilience theory provides a new perspective for homestay tourism rural sustainability research and is of great significance for exploring how rural tourism stakeholders can resist and resolve internal and external disturbances and enhance the capability of sustainable development. To address this issue, we conducted a qualitative and quantitative analysis of data from HTVs, proposed a theoretically hypothetical model of the impact of agglomeration strategy on the resilience of HTV, finding that homestay operators’ agglomeration strategy promoted HTVs’ resilience against environmental changes. Similarly, operators’ willingness to reach a consensus regarding strategic decisions improved rural resilience. Therefore, homestay operators’ agglomeration strategy can have a positive effect on HTVs’ resilience by promoting consensus development. Our findings provide a guideline for homestay tourism and rural resilience in the post-pandemic era.